Resin composition and method for producing connection structure

JP7637320B1Active Publication Date: 2025-02-27SEKISUI CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024566007
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-24
Publication Date
2025-02-27
Estimated Expiration
2044-06-24

AI Technical Summary

Benefits of technology

【0021】 本発明に係る樹脂組成物は、熱硬化性成分と、フラックスと、はんだ粒子と、ゴム粒子とを含み、上記フラックスの平均粒子径が、10μm以下である。本発明に係る樹脂組成物では、上記の構成が備えられているので、高速で飛来する半導体チップの捕捉性を高めることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637320000005
    Figure 0007637320000005
  • Figure 0007637320000006
    Figure 0007637320000006
  • Figure 0007637320000007
    Figure 0007637320000007
Patent Text Reader

Abstract

A resin composition capable of enhancing the ability to capture semiconductor chips (3) flying at high speed is provided. The resin composition (11) according to the present invention contains a thermosetting component (11B), a flux (11D), solder particles (11A) and rubber particles (11C), and the average particle size of the flux is 10 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing solder particles. The present invention also relates to a method for producing a connection structure using the resin composition. [Background technology]

[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive materials, conductive particles are dispersed in a binder. Solder particles are widely used as the conductive particles.

[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of connections using the anisotropic conductive material include connections between a flexible printed circuit board and a glass substrate (FOG (film on glass)), between a semiconductor chip and a flexible printed circuit board (COF (chip on film)), between a semiconductor chip and a glass substrate (COG (chip on glass)), and between a flexible printed circuit board and a glass epoxy substrate (FOB (film on board)).

[0004] In recent years, devices using connection structures have become smaller and lighter. Accordingly, there is a demand for the development of connection structures using fine semiconductor chips such as micro-LED (micro-light emitting diode) chips. Laser transfer methods have attracted attention as a method for placing fine semiconductor chips such as micro-LED chips on circuit boards.

[0005] The following Patent Document 1 discloses a laser transfer device. In this laser transfer device, an original substrate on which multiple elements are formed is placed above a destination substrate. By irradiating the original substrate with laser light from above, multiple transfer target elements, which are the transfer targets among the multiple elements, are moved downward, and the transfer target elements are transferred to the destination substrate.

[0006] The following Patent Document 2 discloses a transfer method for transferring a chip component held on a transfer substrate via a photocurable adhesive layer to a destination substrate. The transfer method includes an exposure step of exposing the adhesive layer to light having a wavelength that hardens the adhesive layer in a pattern to partially reduce the adhesive strength of the adhesive layer, and a laser lift-off step of transferring the chip component to the destination substrate by a laser lift-off method after the exposure step. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] WO2020 / 188780A1 [Patent Document 2] JP 2020-53558 A Summary of the Invention [Problem to be solved by the invention]

[0008] In the method of arranging semiconductor chips using laser transfer, multiple semiconductor chips can be moved and mounted in one go from a wafer substrate (source substrate) to a circuit substrate (destination substrate), thereby increasing the productivity of the connection structure.

[0009] However, in the method of placing a semiconductor chip using the laser transfer method, the semiconductor chip may not be placed accurately in a predetermined place on the circuit board (connection target member) due to the impact when the semiconductor chip, which comes flying at high speed, hits the circuit board (connection target member). If misalignment occurs during placement of the semiconductor chip, it may not be possible to electrically connect the upper and lower electrodes.

[0010] An object of the present invention is to provide a resin composition capable of enhancing the capturing ability of a semiconductor chip flying at high speed. Another object of the present invention is to provide a method for producing a connection structure using the resin composition. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have discovered that by placing a specific resin composition on the surface of a circuit board (a component to be connected), it is possible to effectively capture a semiconductor chip flying at high speed by a laser transfer method or the like.

[0012] Disclosed herein is the following resin composition and a method for producing a connection structure using the resin composition.

[0013] Item 1. A resin composition comprising a thermosetting component, a flux, solder particles, and rubber particles, the flux having an average particle size of 10 μm or less.

[0014] Item 2. A resin composition comprising a thermosetting component, a flux, solder particles, and rubber particles, the resin composition having a tack strength of 150 N or more at 25° C. and 50% RH.

[0015] Item 3. The resin composition according to item 1 or 2, wherein the rubber particles have a glass transition temperature of 25° C. or lower.

[0016] Item 4. The resin composition according to any one of Items 1 to 3, wherein the rubber particles have an average particle size of 1 μm or less.

[0017] Item 5. The resin composition according to any one of Items 1 to 4, wherein the content of the rubber particles is 1% by weight or more and 10% by weight or less in 100% by weight of the resin composition.

[0018] Item 6. The thermosetting component includes a thermosetting compound, and the content of the rubber particles is 2 parts by weight or more and 20 parts by weight or less with respect to 100 parts by weight of the thermosetting compound. The resin composition according to any one of items 1 to 5.

[0019] Item 7. A method for producing a connection structure, comprising: a first arrangement step of using the resin composition according to any one of items 1 to 6 to arrange the resin composition on a surface of a first connection target member having at least one first electrode on its surface; a second arrangement step of moving a second connection target member having at least one second electrode on its surface by a laser transfer method onto a surface of the resin composition opposite to the first connection target member side, and arranging the second connection target member so that the first electrode and the second electrode face each other; and a connection step of forming a connection part connecting the first connection target member and the second connection target member from the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and electrically connecting the first electrode and the second electrode with a solder part in the connection part.

[0020] Item 8. The method for producing a connection structure according to Item 7, wherein in the second arrangement step, the second connection target member is moved by a laser transfer method at a speed of 1 cm / s or more on a surface of the resin composition opposite the first connection target member side, and the second connection target member is arranged so that the first electrode and the second electrode face each other. Effect of the Invention

[0021] The resin composition according to the present invention contains a thermosetting component, a flux, solder particles, and rubber particles, and the average particle size of the flux is 10 μm or less. Since the resin composition according to the present invention has the above-mentioned configuration, it can improve the capture of semiconductor chips flying at high speed.

[0022] The resin composition according to the present invention contains a thermosetting component, flux, solder particles, and rubber particles, and has a tack strength of 150 N or more at 25° C. and 50% RH. Since the resin composition according to the present invention has the above-mentioned configuration, it can improve the capture ability of semiconductor chips flying at high speed. [Brief description of the drawings]

[0023] [Figure 1]FIG. 1 is a cross-sectional view that typically shows a connection structure obtained by using a resin composition according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating the steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view illustrating steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view illustrating steps of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing a modified example of the connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described in detail below.

[0025] (Resin composition) The resin composition according to the present invention includes a thermosetting component, a flux, solder particles, and rubber particles. In the resin composition according to the present invention, the flux has an average particle size of 10 μm or less.

[0026] The resin composition according to the present invention includes a thermosetting component, a flux, solder particles, and rubber particles. The resin composition according to the present invention has a tack strength of 150 N or more at 25° C. and 50% RH.

[0027] Conventionally, in the method of placing semiconductor chips using the laser transfer method, the impact of the semiconductor chip flying at high speed landing on the circuit board (connection target member) can scratch the surface of the circuit board (connection target member) or the semiconductor chip cannot be placed accurately in the specified place on the circuit board (connection target member). If misalignment occurs during placement of the semiconductor chip, it may not be possible to electrically connect the upper and lower electrodes.

[0028] Since the resin composition according to the present invention has the above-mentioned configuration, it is possible to enhance the capture of semiconductor chips arriving at high speed. In particular, it is possible to enhance the capture of semiconductor chips arriving at high speed by the laser transfer method. As a result, it is possible to accurately place the arriving semiconductor chip at a predetermined location on the circuit board (connection target member) (effectively suppressing misalignment during placement of the semiconductor chip).

[0029] In addition, since the resin composition according to the present invention has the above-mentioned configuration, it can absorb the impact when the semiconductor chip lands on the circuit board (the connection target member) and effectively suppress damage to the surface of the circuit board (the connection target member).

[0030] In the present invention, the use of a specific resin composition greatly contributes to obtaining the above-mentioned effects.

[0031] The resin composition is disposed on the surface of a connection target member (circuit board, transfer destination substrate) and used in a method for producing a connection structure. The resin composition is suitably used in a method for producing a connection structure to effectively capture a semiconductor chip flying at high speed by a laser transfer method. The resin composition is preferably a resin composition for capturing a semiconductor chip by a laser transfer method.

[0032] In particular, the resin composition according to the present invention is preferably used for connecting semiconductor chips by a laser transfer method (use of the resin composition for connecting semiconductor chips by a laser transfer method). More specifically, the resin composition according to the present invention is more preferably used for connecting semiconductor chips to a substrate by a laser transfer method (use of the resin composition for connecting semiconductor chips to a substrate by a laser transfer method).

[0033] The tack strength of the resin composition at 25°C and 50% RH is 150N or more. The tack strength of the resin composition at 25°C and 50% RH is preferably 200N or more, more preferably 250N or more, even more preferably 300N or more, and preferably 750N or less, more preferably 700N or less, even more preferably 650N or less. When the tack strength of the resin composition at 25°C and 50% RH is the lower limit or more, the capture ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. When the tack strength of the resin composition at 25°C and 50% RH is the upper limit or less, the resin composition can be applied thinly and well on the surface of the connection target member, and the cohesiveness of the solder during conductive connection can be effectively improved.

[0034] The tack strength of the resin composition at 25° C. and 50% RH can be measured, for example, by the following method. The resin composition is applied to a surface of a glass substrate to a thickness of 250 μm. Using a tack tester (e.g., manufactured by RHESCA), the tack strength is measured under conditions of 25° C. and 50% RH, with a probe diameter of 5.1 mm and a speed of 2.5 mm / min.

[0035] The tack strength of the resin composition at 25° C. and 50% RH can be adjusted by the following methods, etc.: by adjusting the particle size of the flux, by selecting the type of rubber particles, or by adjusting the particle size of the rubber particles.

[0036] The resin composition is preferably in a liquid state at 25°C. A paste state is included in the liquid state. The resin composition is preferably in a paste state at 25°C. The resin composition contains solder particles, and is therefore a conductive material. The resin composition is preferably a conductive paste. The resin composition is preferably a conductive paste at 25°C. In these cases, the resin composition can be applied more thinly and satisfactorily on the surface of the connection target member, the capture of semiconductor chips flying at high speed by the laser transfer method can be more effectively enhanced, and the cohesiveness of the solder during conductive connection can be more effectively enhanced.

[0037] The viscosity (η25) of the resin composition at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 250 Pa·s or less, more preferably 200 Pa·s or less. When the viscosity (η25) is equal to or greater than the lower limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. When the viscosity (η25) is equal to or less than the upper limit, the resin composition can be applied thinly and satisfactorily on the surface of the connection target member, and the cohesiveness of the solder during conductive connection can be effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.

[0038] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE-22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.

[0039] The viscosity (ηmp) of the resin composition at the melting point of the solder particles is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, and preferably 10 Pa·s or less, more preferably 5 Pa·s or less. The viscosity (ηmp) can be appropriately adjusted depending on the type and amount of the blended components. When the viscosity (ηmp) is equal to or more than the lower limit and equal to or less than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively increased, voids at the connection portion can be more effectively suppressed, and the overflow of the resin composition to areas other than the connection portion can be more effectively suppressed. When the viscosity (ηmp) is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between electrodes can be more effectively increased, and the conduction reliability between electrodes can be more effectively increased.

[0040] The viscosity (ηmp) can be measured, for example, using a viscoelasticity measuring device ("HAAKE" manufactured by SCIENTIFIC Corporation) under conditions of stress control of 1 Pa, frequency of 1 Hz, heating rate of 20°C / min, and measurement temperature range of 25°C to 200°C. However, if the melting point of the solder particles exceeds 200°C, the upper temperature limit is set to the melting point of the solder particles. In this measurement, the viscosity (ηmp) is calculated by reading the viscosity at the melting point of the solder particles.

[0041] The resin composition can be used as a conductive paste, a conductive film, and the like. The conductive paste is preferably an anisotropic conductive paste, and the conductive film is preferably an anisotropic conductive film. From the viewpoint of more effectively suppressing positional deviation during arrangement of the connection target components and more effectively enhancing the cohesiveness of the solder during conductive connection, the resin composition is preferably in the form of a paste, and is preferably a conductive paste. The resin composition is suitably used for electrical connection of electrodes. The resin composition is preferably a circuit connection material.

[0042] Each component contained in the resin composition will be described below. In this specification, the term "(meth)acrylate" refers to acrylate and methacrylate. The term "(meth)acrylic" refers to acrylic and methacrylic. The term "(meth)acryloyl" refers to acryloyl and methacryloyl.

[0043] (thermosetting component) The resin composition according to the present invention includes a thermosetting component. The thermosetting component preferably includes a thermosetting compound. The resin composition may or may not include a thermosetting agent as a thermosetting component. Since the resin composition according to the present invention has the above configuration, even if the resin composition does not include a thermosetting agent, it can enhance the capture of a semiconductor chip flying at high speed by a laser transfer method. From the viewpoint of more effectively enhancing the cohesiveness of the solder during conductive connection, it is preferable that the resin composition does not include a thermosetting agent. In order to cure the resin composition more satisfactorily, the resin composition may include a curing accelerator as a thermosetting component.

[0044] (Thermosetting component: thermosetting compound) The resin composition according to the present invention preferably contains a thermosetting compound. The thermosetting compound is a compound that can be cured by heating. The thermosetting compound is not particularly limited. Examples of the thermosetting compound include oxetane compounds, epoxy compounds, episulfide compounds, (meth)acrylic compounds, phenolic compounds, amino compounds, unsaturated polyester compounds, polyurethane compounds, silicone compounds, and polyimide compounds. From the viewpoint of further improving the curability and viscosity of the resin composition and further increasing the conduction reliability, the thermosetting compound is preferably an epoxy compound or an episulfide compound, and more preferably an epoxy compound. The resin composition preferably contains an epoxy compound or an episulfide compound, and more preferably contains an epoxy compound. The thermosetting compound may be used alone or in combination of two or more.

[0045] The epoxy compound is a compound having at least one epoxy group. Examples of the epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, phenol novolac type epoxy compounds, biphenyl type epoxy compounds, biphenyl novolac type epoxy compounds, biphenol type epoxy compounds, naphthalene type epoxy compounds, fluorene type epoxy compounds, phenol aralkyl type epoxy compounds, naphthol aralkyl type epoxy compounds, dicyclopentadiene type epoxy compounds, anthracene type epoxy compounds, epoxy compounds having an adamantane skeleton, epoxy compounds having a tricyclodecane skeleton, naphthylene ether type epoxy compounds, and epoxy compounds having a triazine nucleus in the skeleton. The epoxy compounds may be used alone or in combination of two or more.

[0046] The epoxy compound is liquid or solid at room temperature (25°C), and when the epoxy compound is solid at room temperature, the melting temperature of the epoxy compound is preferably equal to or lower than the melting point of the solder particles. By using the preferred epoxy compound, the viscosity is high at the stage of bonding the connection target components, and when acceleration is applied due to impact during transportation, etc., the positional deviation between the connection target components (circuit board) and the semiconductor chip can be suppressed. Furthermore, the viscosity of the resin composition can be greatly reduced by the heat during curing, and the aggregation of the solder during conductive connection can be efficiently promoted.

[0047] From the viewpoint of more effectively increasing insulation reliability and more effectively increasing conduction reliability, it is preferable that the thermosetting component contains an epoxy compound, and it is preferable that the thermosetting compound contains an epoxy compound.

[0048] From the viewpoint of disposing the solder on the electrodes more effectively, the thermosetting compound preferably contains a thermosetting compound having a polyether skeleton.

[0049] Examples of the thermosetting compound having a polyether skeleton include a compound having a glycidyl ether group at both ends of an alkyl chain having 3 to 12 carbon atoms, and a polyether-type epoxy compound having a polyether skeleton having 2 to 4 carbon atoms and a structural unit in which 2 to 10 polyether skeletons are bonded consecutively.

[0050] From the viewpoint of more effectively increasing the heat resistance of the cured product, the thermosetting compound preferably includes a thermosetting compound having an isocyanuric skeleton.

[0051] Examples of the thermosetting compound having an isocyanuric skeleton include triisocyanurate type epoxy compounds, such as the TEPIC series manufactured by Nissan Chemical Industries, Ltd. (TEPIC-G, TEPIC-S, TEPIC-SS, TEPIC-HP, TEPIC-L, TEPIC-PAS, TEPIC-VL, and TEPIC-UC).

[0052] From the viewpoints of more efficiently disposing the solder on the electrodes, more effectively increasing the reliability of conduction between the upper and lower electrodes to be connected, and more effectively suppressing discoloration of the thermosetting compound, it is preferable that the thermosetting compound has high heat resistance, and more preferably contains a novolac type epoxy compound. Novolac type epoxy compounds have relatively high heat resistance.

[0053] In 100% by weight of the resin composition, the content of the thermosetting compound is preferably 5% by weight or more, more preferably 8% by weight or more, even more preferably 10% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the thermosetting compound is equal to or more than the lower limit and equal to or less than the upper limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of more effectively improving the impact resistance of the resulting connection structure, the content of the thermosetting compound is preferably large.

[0054] In 100% by weight of the resin composition, the content of the epoxy compound is preferably 5% by weight or more, more preferably 8% by weight or more, even more preferably 10% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the epoxy compound is above the lower limit and below the upper limit, the capture of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of further improving the impact resistance of the resulting connection structure, the content of the epoxy compound is preferably high.

[0055] In 100% by weight of the resin composition, the content of the novolac type epoxy compound is preferably 1% by weight or more, more preferably 3% by weight or more, even more preferably 5% by weight or more, and preferably 99% by weight or less, more preferably 90% by weight or less, even more preferably 80% by weight or less, and particularly preferably 70% by weight or less. When the content of the novolac type epoxy compound is above the lower limit and below the upper limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be more effectively improved, the solder can be more efficiently arranged on the electrodes, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. From the viewpoint of further improving the impact resistance of the resulting connection structure, the content of the novolac type epoxy compound is preferably high.

[0056] (Flux) The resin composition contains a flux, which can more effectively increase the cohesion of the solder during conductive connection.

[0057] The flux is not particularly limited, and may be, for example, a flux that is generally used for soldering or the like.

[0058] Examples of the flux include zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic acid, an organic acid amine salt, an organic halide, hydrazine, an amine compound different from the organic acid amine salt, and rosin, etc. Only one type of the flux may be used, or two or more types may be used in combination.

[0059] The molten salt may, for example, be ammonium chloride.

[0060] The organic acids include lactic acid, citric acid, stearic acid, glutamic acid, and glutaric acid.

[0061] Examples of the organic acid amine salt include benzylamine glutaric acid salt, benzylamine adipate salt, benzylamine azelaic acid salt, stearylamine glutaric acid salt, stearylamine adipate salt, and stearylamine azelaic acid salt.

[0062] Examples of the amine compound different from the organic acid amine salt include dicyclohexylamine, benzylamine, benzhydrylamine, imidazole, benzimidazole, phenylimidazole, carboxybenzimidazole, benzotriazole, and carboxybenzotriazole.

[0063] The rosin may be activated rosin or non-activated rosin. The rosin is a rosin containing abietic acid as a main component. The rosin may be abietic acid or acrylic modified rosin.

[0064] From the viewpoint of more efficiently disposing the solder on the electrodes, more effectively increasing the insulation reliability, and more effectively increasing the conduction reliability, the flux preferably contains a salt of an acid compound and a base compound, and more preferably contains an organic acid amine salt. From the viewpoint of more efficiently disposing the solder on the electrodes, more effectively increasing the insulation reliability, and more effectively increasing the conduction reliability, the organic acid amine salt is preferably a carboxylate amine salt, and more preferably an organic acid amine salt having two or more carboxyl groups.

[0065] Examples of the organic acid in the organic acid amine salt having two or more carboxyl groups include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid.

[0066] The acid compound is preferably an organic compound having a carboxyl group. Examples of the acid compound include aliphatic carboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, citric acid, and malic acid, cyclic aliphatic carboxylic acids such as cyclohexyl carboxylic acid and 1,4-cyclohexyl dicarboxylic acid, and aromatic carboxylic acids such as isophthalic acid, terephthalic acid, trimellitic acid, and ethylenediaminetetraacetic acid. From the viewpoint of more efficiently disposing the solder on the electrode, more effectively increasing the insulation reliability, and more effectively increasing the conduction reliability, the acid compound is preferably glutaric acid, cyclohexyl carboxylic acid, or adipic acid.

[0067] The basic compound is preferably an organic compound having an amino group. Examples of the basic compound include diethanolamine, triethanolamine, methyldiethanolamine, ethyldiethanolamine, cyclohexylamine, dicyclohexylamine, benzylamine, benzhydrylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-tert-butylbenzylamine, N-methylbenzylamine, N-ethylbenzylamine, N-phenylbenzylamine, N-tert-butylbenzylamine, N-isopropylbenzylamine, N,N-dimethylbenzylamine, imidazole compounds, and triazole compounds. From the viewpoint of more efficiently disposing the solder on the electrode, more effectively increasing the insulation reliability, and more effectively increasing the conduction reliability, the basic compound is preferably benzylamine.

[0068] The flux is preferably a solid. The flux may be spherical or may have a shape other than spherical, or may be flat.

[0069] The average particle diameter of the flux is 10 μm or less. The average particle diameter of the flux is preferably 7 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. When the average particle diameter of the flux is equal to or less than the upper limit, the capturing ability of semiconductor chips flying at high speed by the laser transfer method can be more effectively improved. The lower limit of the average particle diameter of the flux is not particularly limited. The average particle diameter of the flux may be 0.01 μm or more, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more. The range of the average particle diameter of the flux can be set by appropriately selecting the lower limit value and the upper limit value. In addition, when the flux contains two or more kinds of fluxes, the average particle diameter of the flux indicates the average particle diameter of the entire flux.

[0070] The average particle diameter of the flux is a number average particle diameter. The average particle diameter of the flux is obtained, for example, by observing 50 arbitrary fluxes with an electron microscope or an optical microscope, and calculating the average particle diameter of each flux, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each flux is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary fluxes with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each flux is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the flux is preferably calculated by laser diffraction particle size distribution measurement.

[0071] The flux having an average particle size of 10 μm or less may be a pulverized product of a commercially available flux. Examples of a method for pulverizing a commercially available flux include an agate pulverization method, a jet mill pulverization method, and a bead mill pulverization method.

[0072] The coefficient of variation (CV value) of the particle diameter of the flux is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle diameter of the flux is equal to or less than the upper limit, the flux can be arranged on the electrode more efficiently. The lower limit of the coefficient of variation (CV value) of the particle diameter of the flux is not particularly limited. The coefficient of variation (CV value) of the particle diameter of the flux may be 0% or more, 1% or more, or 5% or more. The range of the coefficient of variation of the particle diameter of the flux can be set by appropriately selecting the lower limit value and the upper limit value.

[0073] The coefficient of variation (CV value) of the particle size of the flux can be measured as follows.

[0074] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of particle size of flux Dn: Average particle size of flux

[0075] The activation temperature (melting point) of the flux is preferably 50° C. or higher, more preferably 70° C. or higher, and even more preferably 80° C. or higher, and is preferably 200° C. or lower, more preferably 190° C. or lower, and even more preferably 180° C. or lower. When the activation temperature of the flux is equal to or higher than the lower limit and equal to or lower than the upper limit, the flux effect is more effectively exerted, and the solder is more efficiently arranged on the electrode. The activation temperature (melting point) of the flux is preferably 70° C. or higher and 190° C. or lower, and particularly preferably 80° C. or higher and 180° C. or lower.

[0076] The activation temperature (melting point) of the flux can be determined by differential scanning calorimetry (DSC). An example of a DSC device is "EXSTAR DSC7020" manufactured by SII Corporation.

[0077] Examples of the flux having an active temperature (melting point) of 80° C. or higher and 180° C. or lower include dicarboxylic acids such as glutaric acid (melting point 96° C.), glutaric acid benzylamine salt (melting point 108° C.), adipic acid (melting point 152° C.), adipic acid benzylamine salt (melting point 180° C.), pimelic acid (melting point 104° C.), and suberic acid (melting point 142° C.), benzoic acid (melting point 122° C.), and malic acid (melting point 130° C.).

[0078] The flux preferably has a boiling point of 200° C. or lower.

[0079] The flux may be dispersed in the resin composition, or may be attached to the surfaces of the solder particles.

[0080] The flux is preferably one that releases cations when heated. By using a flux that releases cations when heated, the solder can be placed on the electrodes more efficiently.

[0081] In 100% by weight of the resin composition, the content of the flux is preferably 0.5% by weight or more, more preferably 1% by weight or more, even more preferably 5% by weight or more, particularly preferably 10% by weight or more, and is preferably 30% by weight or less, more preferably 25% by weight or less. When the content of the flux is equal to or more than the lower limit and equal to or less than the upper limit, it becomes even more difficult for an oxide film to be formed on the surfaces of the solder and the electrodes, and further, the oxide film formed on the surfaces of the solder and the electrodes can be removed more effectively.

[0082] (solder particles) The resin composition includes solder particles. The solder particles are formed of solder at both the center and the outer surface. The solder particles are particles in which both the center and the outer surface are solder. When conductive particles having a base particle formed of a material other than solder and a solder portion arranged on the surface of the base particle are used instead of the solder particles, the conductive particles are less likely to gather on the electrode. In addition, the conductive particles have low solder bonding between the conductive particles, so that the conductive particles that have moved onto the electrode tend to move out of the electrode.

[0083] The solder is preferably a metal (low melting point metal) having a melting point of 450°C or less. The solder particles are preferably metal particles (low melting point metal particles) having a melting point of 450°C or less. The low melting point metal particles are particles containing a low melting point metal. The low melting point metal refers to a metal having a melting point of 450°C or less. The melting point of the low melting point metal is preferably 300°C or less, more preferably 220°C or less, and even more preferably 190°C or less.

[0084] The melting point of the solder particles is preferably 100° C. or higher, more preferably 105° C. or higher, and preferably 250° C. or lower, more preferably 245° C. or lower. When the melting point of the solder particles is equal to or higher than the lower limit and equal to or lower than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively improved. When the melting point of the solder particles is equal to or higher than the lower limit and equal to or lower than the upper limit, when electrodes are electrically connected, the conductivity reliability can be more effectively improved and the insulation reliability can be more effectively improved.

[0085] The melting point of the solder particles can be determined by differential scanning calorimetry (DSC), such as the "EXSTAR DSC7020" manufactured by SII Corporation.

[0086] The solder particles preferably contain 90% or more by weight of solder in 100% by weight of the solder particles. The solder particles also preferably contain tin. In 100% by weight of the metals contained in the solder particles, the tin content is preferably 30% or more by weight, more preferably 40% or more by weight, even more preferably 70% or more by weight, and particularly preferably 90% or more by weight. When the tin content in the solder particles is equal to or greater than the lower limit, the connection reliability between the solder portion and the electrode can be more effectively improved.

[0087] The tin content can be measured using a high-frequency inductively coupled plasma atomic emission spectrometer ("ICP-AES" manufactured by Horiba, Ltd.) or a fluorescent X-ray analyzer ("EDX-800HS" manufactured by Shimadzu Corporation).

[0088] By using the solder particles, the solder melts and bonds to the electrodes, and the solder portion conducts electricity between the electrodes. For example, the solder portion and the electrodes are easily in surface contact rather than point contact, so that the connection resistance is reduced. In addition, the use of the solder particles increases the bonding strength between the solder portion and the electrodes, so that the solder portion and the electrodes are less likely to peel off, and the reliability of the conduction and the reliability of the connection can be more effectively improved.

[0089] The low melting point metal constituting the solder particles is not particularly limited. The low melting point metal is preferably tin or an alloy containing tin. Examples of the alloy include a tin-silver alloy, a tin-copper alloy, a tin-silver-copper alloy, a tin-bismuth alloy, a tin-zinc alloy, and a tin-indium alloy. Since the low melting point metal has excellent wettability with respect to the electrode, it is preferable that the low melting point metal is tin, a tin-silver alloy, a tin-silver-copper alloy, a tin-bismuth alloy, or a tin-indium alloy. It is more preferable that the low melting point metal is a tin-bismuth alloy or a tin-indium alloy.

[0090] The solder particles are preferably a filler metal having a liquidus temperature of 450° C. or less based on JIS Z3001: Welding Terminology. Examples of the composition of the solder particles include metal compositions containing zinc, gold, silver, lead, copper, tin, bismuth, indium, etc. The solder particles preferably do not contain lead, and preferably contain tin and indium, or tin and bismuth.

[0091] In order to more effectively increase the bonding strength between the solder part and the electrode, the solder particles may contain metals such as nickel, copper, antimony, aluminum, zinc, iron, gold, titanium, phosphorus, germanium, tellurium, cobalt, bismuth, manganese, chromium, molybdenum, and palladium. In order to more effectively increase the bonding strength between the solder part and the electrode, the solder particles preferably contain nickel, copper, antimony, aluminum, or zinc. In order to more effectively increase the bonding strength between the solder part and the electrode, the content of these metals for increasing the bonding strength is preferably 0.0001% by weight or more, and preferably 1% by weight or less, based on 100% by weight of the metal contained in the solder particles.

[0092] The average particle diameter of the solder particles is preferably 0.01 μm or more, more preferably 0.03 μm or more. When the average particle diameter of the solder particles is equal to or more than the lower limit, the solder can be arranged on the electrode more efficiently. The average particle diameter of the solder particles may be equal to or less than 5 μm, or may be equal to or less than 3 μm. The range of the average particle diameter of the solder particles can be set by appropriately selecting the lower limit and the upper limit.

[0093] The average particle diameter of the solder particles is a number average particle diameter. The average particle diameter of the solder particles is obtained, for example, by observing 50 arbitrary solder particles with an electron microscope or an optical microscope and calculating the average particle diameter of each solder particle, or by performing laser diffraction type particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each solder particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary solder particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction type particle size distribution measurement, the particle diameter of each solder particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the solder particles is preferably calculated by laser diffraction type particle size distribution measurement.

[0094] The coefficient of variation (CV value) of the particle diameter of the solder particles is preferably 5% or more, more preferably 10% or more, and is preferably 40% or less, more preferably 30% or less. When the coefficient of variation of the particle diameter of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrode more efficiently. However, the CV value of the particle diameter of the solder particles may be less than 5%.

[0095] The coefficient of variation (CV value) can be measured as follows.

[0096] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of solder particle diameter Dn: Average particle size of solder particles

[0097] The shape of the solder particles is not particularly limited, and may be spherical, may be a shape other than spherical, or may be flat.

[0098] In 100% by weight of the resin composition, the content of the solder particles is preferably 1% by weight or more, more preferably 2% by weight or more, even more preferably 10% by weight or more, particularly preferably 20% by weight or more, most preferably 30% by weight or more, and preferably 80% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less. When the content of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be arranged on the electrodes more efficiently, it is easy to arrange a large amount of solder between the electrodes, and the electrical reliability can be improved more effectively. From the viewpoint of improving the electrical reliability more effectively, the content of the solder particles is preferably large.

[0099] (rubber particles) The resin composition includes rubber particles. The rubber particles are preferably not dissolved in a solvent such as an organic solvent. The rubber particles are preferably not compatible with components in the resin composition such as a thermosetting component. In the resin composition, the rubber particles are preferably present in a dispersed state. During conductive connection, the rubber particles preferably do not inhibit the aggregation of solder particles. During conductive connection, the rubber particles are preferably not incorporated into the solder part (solder solidified product formed by the aggregation of the molten solder particles after the solder particles melt). The rubber particles may be particles having a core-shell structure, or may be particles not having a core-shell structure. The core-shell structure is a structure including a core and a shell disposed on the surface of the core. When the rubber particles are particles having the core-shell structure, it is preferable that the compound constituting the core and the compound constituting the shell are chemically bonded at the interface between the core and the shell. The chemical bond is preferably a graft bond. The rubber particles may be one type only, or two or more types may be used in combination.

[0100] The material of the rubber particles is not particularly limited. Examples of the material of the rubber particles include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; (meth)acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. Examples of the divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer. The rubber particles are preferably polymerized from one or more types of polymerizable monomers having an ethylenically unsaturated group, since this allows the hardness of the rubber particles to be easily controlled within a suitable range.

[0101] When the rubber particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.

[0102] Examples of the non-crosslinkable monomer include styrene-based monomers such as styrene and α-methylstyrene; carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and the like. Examples of the monomers include oxygen-containing (meth)acrylate compounds such as acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; unsaturated hydrocarbons such as ethylene, propylene, isoprene, and butadiene; and halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, and chlorostyrene.

[0103] Examples of the crosslinkable monomer include tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly) Examples of suitable (meth)acrylates include polyfunctional (meth)acrylate compounds such as propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and silane-containing monomers such as triallyl (iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, and vinyltrimethoxysilane.

[0104] The rubber particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group by a known method, such as a method of suspension polymerization in the presence of a radical polymerization initiator, and a method of swelling and polymerizing a monomer together with a radical polymerization initiator using non-crosslinked seed particles.

[0105] The rubber particles preferably include divinylbenzene polymer particles, silicone rubber particles, polybutadiene rubber particles, or acrylic rubber particles, more preferably divinylbenzene polymer particles, polybutadiene rubber particles, or acrylic rubber particles, and even more preferably polybutadiene rubber particles, or acrylic rubber particles. By using these rubber particles, the ability to capture semiconductor chips flying at high speed by the laser transfer method can be further improved.

[0106] The glass transition temperature of the rubber particles is preferably -90°C or higher, more preferably -75°C or higher, even more preferably -60°C or higher, and preferably 25°C or lower, more preferably 15°C or lower, even more preferably 5°C or lower, and particularly preferably -5°C or lower. When the glass transition temperature of the rubber particles is above the lower limit, the positional deviation of the connection target component when it is arranged can be more efficiently suppressed. When the glass transition temperature of the rubber particles is below the upper limit, the cohesiveness of the solder during conductive connection can be more effectively increased, and the rubber particles can be effectively prevented from being taken into the solder portion.

[0107] The glass transition temperature of the rubber particles can be measured using a dynamic viscoelasticity measurement device ("ARES-G2" manufactured by TA Instruments) or the like.

[0108] The average particle diameter of the rubber particles is preferably 1 μm or less, more preferably 0.8 μm or less, and even more preferably 0.5 μm or less. The lower limit of the average particle diameter of the rubber particles is not particularly limited. The average particle diameter of the rubber particles may be 0.03 μm or more, or may be 0.1 μm or more. When the average particle diameter of the rubber particles is equal to or less than the upper limit, the positional deviation of the connection target component when it is arranged can be more effectively suppressed. When the average particle diameter of the rubber particles is equal to or less than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively increased, and the rubber particles can be effectively prevented from being taken into the solder portion. By effectively preventing the rubber particles from being taken into the solder portion, the electrical reliability can be more effectively improved. The range of the particle diameter of the rubber particles can be set by appropriately selecting the lower limit value and the upper limit value.

[0109] The average particle diameter of the rubber particles is the number average particle diameter. The average particle diameter of the rubber particles is obtained, for example, by observing 50 arbitrary rubber particles with an electron microscope or an optical microscope, and calculating the average particle diameter of each rubber particle, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each rubber particle is obtained as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary solder particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each rubber particle is obtained as the particle diameter of a sphere equivalent diameter. The average particle diameter of the rubber particles is preferably calculated by laser diffraction particle size distribution measurement.

[0110] In the resin composition, the ratio of the average particle diameter of the rubber particles to the average particle diameter of the solder particles (average particle diameter of rubber particles / average particle diameter of solder particles) is preferably 3.0 or less, more preferably 2.0 or less. The lower limit of the ratio (average particle diameter of rubber particles / average particle diameter of solder particles) is not particularly limited. The ratio (average particle diameter of rubber particles / average particle diameter of solder particles) may be 0.001 or more. When the ratio (average particle diameter of rubber particles / average particle diameter of solder particles) is equal to or greater than the lower limit and equal to or less than the upper limit, the positional deviation during arrangement of the connection target components can be more effectively suppressed. When the ratio (average particle diameter of rubber particles / average particle diameter of solder particles) is equal to or greater than the lower limit and equal to or less than the upper limit, the cohesiveness of the solder during conductive connection can be more effectively increased, and the incorporation of the rubber particles into the solder portion can be effectively prevented. By effectively preventing the incorporation of the rubber particles into the solder portion, the electrical reliability can be more effectively improved. The range of the above ratio (average particle size of rubber particles / average particle size of solder particles) can be set by appropriately selecting the above lower limit value and the above upper limit value.

[0111] In the particle size distribution of the rubber particles on a volume basis, the D90 of the rubber particles is preferably 3 μm or less, more preferably 2 μm or less, and further preferably 1 μm or less. The lower limit of the D90 of the rubber particles is not particularly limited. The D90 of the rubber particles may be 0.01 μm or more, or may be 0.03 μm or more. In addition, in the particle size distribution of the rubber particles on a volume basis, if the D90 of the rubber particles is equal to or less than the upper limit, the gap between the connection target components becomes even smaller. The range of the D90 of the rubber particles can be set by appropriately selecting the lower limit value and the upper limit value.

[0112] The D90 of the rubber particles is the particle size of the rubber particles when the cumulative volume of the rubber particles is 90%. The D90 of the rubber particles can be calculated from the particle size distribution on a volume basis.

[0113] The volumetric particle size distribution of the rubber particles is determined using a laser diffraction particle size distribution analyzer, such as Malvern's "Mastersizer 3000."

[0114] In 100% by weight of the resin composition, the content of the rubber particles is preferably 0.5% by weight or more, more preferably 1% by weight or more, even more preferably 1.5% by weight or more, and preferably 10% by weight or less, more preferably 8% by weight or less, even more preferably 5% by weight or less, and particularly preferably 4% by weight or less. When the content of the rubber particles is equal to or more than the lower limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. When the content of the rubber particles is equal to or less than the upper limit, the resin composition can be applied thinly and well on the surface of the connection target member.

[0115] The content of the rubber particles is preferably 1 part by weight or more, more preferably 2 parts by weight or more, and even more preferably 3 parts by weight or more, and is preferably 20 parts by weight or less, more preferably 16 parts by weight or less, and even more preferably 10 parts by weight or less, relative to 100 parts by weight of the thermosetting component. When the content of the rubber particles is equal to or more than the lower limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. When the content of the rubber particles is equal to or less than the upper limit, the resin composition can be applied thinly and well on the surface of the connection target member.

[0116] When the thermosetting component contains the thermosetting compound, the content of the rubber particles is preferably 2 parts by weight or more, more preferably 4 parts by weight or more, even more preferably 6 parts by weight or more, and preferably 20 parts by weight or less, more preferably 16 parts by weight or less, and even more preferably 10 parts by weight or less, relative to 100 parts by weight of the thermosetting compound. When the content of the rubber particles is equal to or more than the lower limit, the capturing ability of the semiconductor chip flying at high speed by the laser transfer method can be further improved. When the content of the rubber particles is equal to or less than the upper limit, the resin composition can be applied thinly and well on the surface of the connection target member.

[0117] (Filler) The resin composition may contain a filler. The filler may be an organic filler or an inorganic filler. By adding the filler, the solder can be more uniformly aggregated on all the electrodes of the connection target member.

[0118] The resin composition preferably does not contain the filler or contains the filler in an amount of 5% by weight or less. When the resin composition contains the thermosetting compound, the smaller the filler content, the easier it is for the solder particles to move onto the electrodes.

[0119] In 100% by weight of the resin composition, the content of the filler is preferably 5% by weight or less, more preferably 2% by weight or less, even more preferably 1% by weight or less, and most preferably 0% by weight (not contained). When the content of the filler is equal to or less than the upper limit, the solder is more uniformly arranged on the electrode.

[0120] (Other ingredients) The above-mentioned resin composition may contain various additives, as necessary, such as an extender, a softener, a plasticizer, a thickener, a thixotropic agent, a leveling agent, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.

[0121] (Connection structure and method for manufacturing the connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the material of the connection part is the above-mentioned resin composition. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by a solder part in the connection part.

[0122] In the connection structure according to the present invention, a specific resin composition is used, so that the solder is easily collected between the first electrode and the second electrode, and the solder can be efficiently arranged on the electrodes (lines). In addition, a part of the solder is unlikely to be arranged in an area (space) where no electrodes are formed, and the amount of solder arranged in the area where no electrodes are formed can be significantly reduced. Therefore, the reliability of the conduction between the first electrode and the second electrode can be improved. Moreover, it is possible to prevent electrical connection between laterally adjacent electrodes that should not be connected, and to improve the reliability of insulation.

[0123] In addition, in order to efficiently place the solder on the electrodes and significantly reduce the amount of solder placed in areas where no electrodes are formed, it is preferable to use a conductive paste rather than a conductive film as the resin composition.

[0124] In the connection structure, it is preferable that the first connection target member is a circuit board, and in the connection structure, it is preferable that the second connection target member is a semiconductor chip.

[0125] The method for producing a connection structure according to the present invention comprises the following steps: (1) a first arrangement step of using the above-mentioned resin composition to arrange the resin composition on a surface of a first connection target member having at least one first electrode on its surface; (2) a second arrangement step of moving a second connection target member having at least one second electrode on its surface onto a surface of the resin composition opposite the first connection target member side by a laser transfer method, and arranging the second connection target member so that the first electrode and the second electrode face each other; and (3) a connection step of forming a connection part connecting the first connection target member and the second connection target member from the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and electrically connecting the first electrode and the second electrode by a solder part in the connection part.

[0126] Since the method for manufacturing a connection structure according to the present invention has the above-mentioned configuration, it is possible to improve the capture of the second connection target component (semiconductor chip) that arrives at high speed by the laser transfer method.

[0127] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings.

[0128] FIG. 1 is a cross-sectional view that typically shows a connection structure obtained by using a resin composition according to one embodiment of the present invention.

[0129] 1 includes a first connection target member 2, a second connection target member 3, and a connection part 4 connecting the first connection target member 2 and the second connection target member 3. The connection part 4 is formed from the above-mentioned resin composition.

[0130] In this embodiment, the resin composition includes a thermosetting component, a flux, solder particles, and rubber particles. The flux includes a flux having an average particle diameter of 10 μm or less. In this embodiment, a conductive paste is used as the resin composition.

[0131] The connection portion 4 has a solder portion 4A in which a plurality of solder particles are gathered and joined together, and a cured portion 4B in which a thermosetting component is thermally cured.

[0132] The rubber particles are preferably present in the cured portion 4 B. However, a small amount of the rubber particles may be present in the solder portion 4 A.

[0133] The first connection target member 2 has a plurality of first electrodes 2a on its surface (upper surface). The second connection target member 3 has a plurality of second electrodes 3a on its surface (lower surface). The first electrode 2a and the second electrode 3a are electrically connected by the solder portion 4A. Therefore, the first connection target member 2 and the second connection target member 3 are electrically connected by the solder portion 4A. In the connection portion 4, solder is not present in a region (hardened portion 4B) other than the solder portion 4A gathered between the first electrode 2a and the second electrode 3a. In a region (hardened portion 4B) other than the solder portion 4A, solder is not present apart from the solder portion 4A. In addition, if the amount is small, solder may be present in a region (hardened portion 4B) other than the solder portion 4A gathered between the first electrode 2a and the second electrode 3a.

[0134] As shown in FIG. 1, in the connection structure 1, a plurality of solder particles are gathered between the first electrode 2a and the second electrode 3a, and after the plurality of solder particles melt, the molten solder particles wet and spread over the surface of the electrode, and then solidify to form the solder portion 4A. Therefore, the connection area between the solder portion 4A and the first electrode 2a, and between the solder portion 4A and the second electrode 3a is increased. That is, by using the solder particles, the contact area between the solder portion 4A and the first electrode 2a, and between the solder portion 4A and the second electrode 3a is increased compared to the case where the outer surface portion of the conductive portion is made of a metal such as nickel, gold, or copper. Therefore, the conduction reliability and connection reliability of the connection structure 1 are increased. In addition, the flux contained in the resin composition is generally gradually deactivated by heating.

[0135] In the connection structure 1 shown in FIG. 1, all of the solder portion 4A is located in the opposing region between the first and second electrodes 2a, 3a. The connection structure 1X of the modified example shown in FIG. 5 differs from the connection structure 1 shown in FIG. 1 only in the connection portion 4X. The connection portion 4X has a solder portion 4XA and a hardened portion 4XB. Like the connection structure 1X, most of the solder portion 4XA is located in the opposing region of the first and second electrodes 2a, 3a, and a part of the solder portion 4XA may protrude laterally from the opposing region of the first and second electrodes 2a, 3a. The solder portion 4XA protruding laterally from the opposing region of the first and second electrodes 2a, 3a is a part of the solder portion 4XA, and is not solder separated from the solder portion 4XA. In this embodiment, the amount of solder separated from the solder portion can be reduced, but the solder separated from the solder portion may be present in the hardened portion.

[0136] If the amount of solder particles used is reduced, it becomes easier to obtain the connection structure 1. If the amount of solder particles used is increased, it becomes easier to obtain the connection structure 1X.

[0137] The thickness of the solder portion between the first electrode and the second electrode is preferably 10 μm or more, more preferably 20 μm or more, and preferably 100 μm or less, more preferably 80 μm or less. In the first electrode and the second electrode, the solder wetted area on the surface of the electrode (the area in contact with the solder in 100% of the exposed area of ​​the electrode) is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and preferably 100% or less. When the solder portion in the connection satisfies the above-mentioned preferable aspects, the electrical continuity reliability and the insulation reliability can be further effectively improved.

[0138] In the connection structure 1, 1X, when the opposing portion of the first electrode 2a and the second electrode 3a is viewed in the stacking direction of the first electrode 2a, the connection portion 4, 4X, and the second electrode 3a, it is preferable that the solder portion 4A, 4XA in the connection portion 4, 4X is disposed in 50% or more of the 100% area of ​​the opposing portion of the first electrode 2a and the second electrode 3a. When the solder portion 4A, 4XA in the connection portion 4, 4X satisfies the above-mentioned preferable aspect, the electrical connection reliability can be further improved.

[0139] When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is preferably arranged in 50% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is more preferably arranged in 60% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. When the portion where the first electrode and the second electrode face each other is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode, the solder portion in the connection portion is further preferably arranged in 70% or more of the 100% area of ​​the portion where the first electrode and the second electrode face each other. It is particularly preferable that the solder portion in the connection portion is disposed in 80% or more of the 100% area of ​​the facing portion of the first electrode and the second electrode when the facing portion of the first electrode and the second electrode is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode. It is most preferable that the solder portion in the connection portion is disposed in 90% or more of the 100% area of ​​the facing portion of the first electrode and the second electrode when the facing portion of the first electrode and the second electrode is viewed in the stacking direction of the first electrode, the connection portion, and the second electrode. When the solder portion in the connection portion satisfies the above-mentioned preferable aspects, the electrical connection reliability can be further improved.

[0140] When the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode, it is preferable that 60% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other. It is more preferable that 70% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode. It is even more preferable that 90% or more of the solder portion in the connection portion is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection portion, and the second electrode. It is particularly preferable that 95% or more of the solder in the connection part is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection part, and the second electrode. It is most preferable that 99% or more of the solder in the connection part is disposed in the portion where the first electrode and the second electrode face each other when the portion where the first electrode and the second electrode face each other is viewed in a direction perpendicular to the stacking direction of the first electrode, the connection part, and the second electrode. When the solder in the connection part satisfies the above-mentioned preferable aspect, the electrical connection reliability can be further improved.

[0141] Next, an example of a method for producing a connection structure 1 using a resin composition according to one embodiment of the present invention will be described with reference to Figures 2 to 4. Figures 2 to 4 are cross-sectional views for explaining each step of an example of a method for producing a connection structure using a resin composition according to one embodiment of the present invention.

[0142] First, a first connection target member (circuit board) 2 having a first electrode 2a on its surface (upper surface) is prepared. Next, as shown in Fig. 2, a resin composition 11 containing a thermosetting component 11B, solder particles 11A, rubber particles 11C, and flux 11D is placed on the surface of the first connection target member (circuit board) 2 (first placing step). The thermosetting component 11B contains a thermosetting compound.

[0143] A resin composition 11 is placed on the surface of the first connection target member (circuit board) 2 on which the first electrode 2a is provided. After placing the resin composition 11, solder particles 11A, rubber particles 11C, and flux 11D are placed on both the first electrode 2a (lines) and the area (space) where the first electrode 2a is not formed. The resin composition may be placed only on the surface of the first electrode.

[0144] There is no particular limitation on the method for disposing the resin composition 11. Examples of the method for disposing the resin composition 11 include application by a dispenser, screen printing, and ejection by an inkjet device.

[0145] Also, a second connection target member (semiconductor chip) 3 having a second electrode 3a on its surface (lower surface) is prepared. The second connection target member (semiconductor chip) 3 having the second electrode 3a on its surface (lower surface) is disposed on the surface of the support film 6 side of the transfer source substrate including a support member 5 and a support film 6. The second connection target member (semiconductor chip) 3 having the second electrode 3a on its surface (lower surface) is disposed on the surface of the support film 6.

[0146] Next, as shown in FIG. 3, in the resin composition 11 on the surface of the first connection target member (circuit board) 2, the second connection target member (semiconductor chip) 3 is moved by a laser transfer method onto the surface of the resin composition 11 opposite to the first connection target member (circuit board) 2 side, and the second connection target member (semiconductor chip) 3 is placed (second placement step). The second connection target member (semiconductor chip) 3 is placed on the surface of the resin composition 11 from the second electrode 3a side. In the second placement step, a laser is irradiated from the support member 5 side of the transfer source substrate by the laser irradiation device 51, so that the curing reaction of the curable component (resin component) in the support film 6 progresses, and the adhesive force of the surface of the support film 6 is greatly reduced. As a result, the second connection target member (semiconductor chip) 3 is peeled off from the transfer source substrate (particularly, the support film 6) and moved onto the surface of the resin composition 11 opposite to the first connection target member (circuit board) 2 side. The second connection target member (semiconductor chip) 3 moves by itself, for example, in a state where the surface of the second connection target member (semiconductor chip) 3 is not in contact with other members (is not held by other members). At this time, the first electrode 2a and the second electrode 3a face each other.

[0147] In this embodiment, since the resin composition is used, the second connection target member (semiconductor chip) 3 flying at high speed by the laser transfer method can be captured more easily in the second placement step. As a result, the flying second connection target member (semiconductor chip) can be accurately placed at a predetermined location on the first connection target member (circuit board) (effectively suppressing misalignment during placement of the semiconductor chip).

[0148] In addition, since the above-mentioned resin composition is used in this embodiment, the impact when the second connection target component (semiconductor chip) lands on the first connection target component (circuit board) can be absorbed, and scratches on the surface of the first connection target component (circuit board) can be effectively suppressed.

[0149] Next, the resin composition 11 is heated to a temperature equal to or higher than the melting point of the solder particles 11A. Preferably, the resin composition 11 is heated to a temperature equal to or higher than the curing temperature of the thermosetting component 11B (thermosetting compound). During this heating, the solder particles 11A that existed in the region where no electrode is formed gather between the first electrode 2a and the second electrode 3a (self-aggregation effect). When a conductive paste is used instead of a conductive film, the solder particles 11A gather more effectively between the first electrode 2a and the second electrode 3a. In addition, the solder particles 11A melt and bond to each other. In addition, the thermosetting component 11B is thermally cured. As a result, as shown in FIG. 4, a connection portion 4 that connects the first connection target member (circuit board) 2 and the second connection target member (semiconductor chip) 3 is formed by the resin composition 11. The connection part 4 is formed by the resin composition 11, the solder part 4A is formed by bonding the multiple solder particles 11A, the thermosetting component 11B is thermally cured to form the hardened part 4B, and the first electrode 2a and the second electrode 3a are electrically connected by the solder part 4A in the connection part 4 (connection step). If the solder particles 11A move sufficiently, it is not necessary to keep the temperature constant from the start of the movement of the solder particles 11A that are not located between the first electrode 2a and the second electrode 3a until the movement of the solder particles 11A between the first electrode 2a and the second electrode 3a is completed.

[0150] It is preferable not to apply pressure in the second arrangement step and the connection step. In this case, the weight of the second connection target member (semiconductor chip) 3 is added to the resin composition 11. Therefore, when the connection part 4 is formed, the solder particles 11A gather more effectively between the first electrode 2a and the second electrode 3a. If pressure is applied in at least one of the second arrangement step and the connection step, the action of the solder particles 11A to gather between the first electrode 2a and the second electrode 3a tends to be inhibited.

[0151] In addition, since no pressure is applied in this embodiment, even if the first connection target member (circuit board) 2 and the second connection target member (semiconductor chip) 3 are superimposed with the first electrode 2a and the second electrode 3a slightly misaligned, the first electrode 2a and the second electrode 3a can be connected by correcting the slight misalignment (self-alignment effect). This is because the molten solder self-aggregating between the first electrode 2a and the second electrode 3a is energetically more stable when the contact area between the solder between the first electrode 2a and the second electrode 3a and the other components of the resin composition is minimized, and a force acts to make the connection structure with the minimum area, which is an aligned connection structure. At this time, it is desirable that the resin composition is not cured, and that the viscosity of the components of the resin composition other than the solder particles is sufficiently low at that temperature and time.

[0152] In this manner, the connection structure 1 shown in FIG. 1 is obtained. The second arrangement step and the connection step may be performed consecutively. After the second arrangement step, the resulting laminate of the first connection target member 2, the resin composition 11, and the second connection target member 3 may be moved to a heating section to perform the connection step. To perform the heating, the laminate may be placed on a heating member, or the laminate may be placed in a heated space.

[0153] In the second arrangement step, it is preferable to move the second connection target member on the surface of the resin composition opposite to the first connection target member side by a laser transfer method at a speed of 1 cm / s or more, and arrange the second connection target member so that the first electrode and the second electrode face each other. In the second arrangement step, the speed at which the second connection target member is moved by the laser transfer method on the surface of the resin composition opposite to the first connection target member side is preferably 5 cm / s or more, more preferably 10 cm / s or more, and even more preferably 50 cm / s or more. The upper limit of the speed at which the second connection target member is moved by the laser transfer method is not particularly limited. In the laser transfer method in the second arrangement step, the second connection target member may be moved on the surface of the resin composition opposite to the first connection target member side at a speed of 500 cm / s or less. In the second placement step, the range of the speed at which the second connection target component is moved by a laser transfer method onto the surface of the resin composition opposite the first connection target component side can be set by appropriately selecting the lower limit value and the upper limit value.

[0154] The heating temperature in the connecting step is preferably 250° C. or more, more preferably 300° C. or more, and preferably 450° C. or less, more preferably 400° C. or less, and even more preferably 350° C. or less. When the heating temperature in the connecting step is equal to or more than the lower limit and equal to or less than the upper limit, the solder can be more efficiently disposed on the electrodes, and the reliability of conductivity between the upper and lower electrodes to be connected can be more effectively improved.

[0155] Heating methods for the above-mentioned connection process include a method of heating the entire connection structure using a reflow furnace or oven to a temperature above the melting point of the solder and above the curing temperature of the thermosetting component, and a method of locally heating only the connection portion of the connection structure.

[0156] Examples of tools used in the localized heating method include a hot plate, a heat gun that applies hot air, a soldering iron, and an infrared heater.

[0157] In addition, when applying localized heating using a hot plate, it is preferable to form the upper surface of the hot plate from a metal with high thermal conductivity directly below the connection portion, and from a material with low thermal conductivity such as a fluororesin for other areas where it is not desirable to heat the connection portion.

[0158] The first and second connection target members are not particularly limited. Examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The semiconductor chip may be an LED chip, and the semiconductor package may be an LED package. The second connection target member is preferably an electronic component. The second connection target member is preferably a semiconductor chip, more preferably an LED chip, and even more preferably a micro LED chip.

[0159] At least one of the first connection target member and the second connection target member is preferably a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate. The first connection target member is preferably a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate. Resin films, flexible printed circuit boards, flexible flat cables, and rigid flexible substrates have the properties of being highly flexible and relatively lightweight. When a conductive film is used to connect such connection target members, solder tends not to gather on the electrodes. In contrast, by using a conductive paste, even if a resin film, a flexible printed circuit board, a flexible flat cable, or a rigid flexible substrate is used, solder can be efficiently gathered on the electrodes, thereby sufficiently increasing the reliability of conduction between the electrodes.

[0160] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.

[0161] The support member is not particularly limited, and examples of the support member include a glass substrate, a sapphire substrate, a silicone substrate, a metal substrate, and an organic substrate.

[0162] The support film is not particularly limited. Examples of the support film include a silicone resin film, an acrylic resin film, and a polyimide resin film. The support film preferably has an adhesive layer.

[0163] In the second disposing step, the integrated light amount of the irradiated laser is preferably 100 mJ / cm 2 More preferably, 150 mJ / cm 2 More preferably, 200 mJ / cm 2 or more, preferably 400 mJ / cm 2 Less than or equal to 350 mJ / cm 2 Less than 300 mJ / cm, more preferably 300 mJ / cm 2 When the integrated light amount of the laser irradiated in the second placing step is equal to or more than the lower limit and equal to or less than the upper limit, the ability to capture semiconductor chips flying at high speed can be further improved.

[0164] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0165] Thermosetting component (thermosetting compound): Phenol novolac type epoxy compound ("JER152" manufactured by Mitsubishi Chemical Corporation) Hydrogenated bisphenol A epoxy compound (Mitsubishi Chemical Corporation "YX8000") Bisphenol F type epoxy compound (DIC "830-S")

[0166] Flux: Adipic acid benzylamine salt 1 (average particle size 5 μm, melting point 180° C., prepared according to Synthesis Example 1 below) Adipic acid benzylamine salt 2 (average particle size 10 μm, melting point 180° C., prepared according to Synthesis Example 1 below) Adipic acid benzylamine salt 3 (average particle size 30 μm, melting point 180° C., prepared according to Synthesis Example 1 below) Glutaric acid benzylamine salt (average particle size 10 μm, melting point 108° C., prepared according to Synthesis Example 2 below)

[0167] Synthesis example 1: In a glass bottle, 24 g of water as a reaction solvent and 14.612 g of adipic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed and heated at 100°C for 10 minutes to dissolve. Then, 10.715 g of benzylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed and stirred for about 5 minutes to obtain a mixed solution. The obtained mixed solution was placed in a refrigerator at 5°C to 10°C and left overnight. The precipitated crystals were separated by filtration, washed with water, and vacuum dried to obtain benzylamine adipate salt 3 (average particle size 30 μm). The obtained benzylamine adipate salt 3 was pulverized by a jet mill pulverization method to obtain benzylamine adipate salt 1 with an average particle size of 5 μm and benzylamine adipate salt 2 with an average particle size of 10 μm.

[0168] Synthesis example 2: In a glass bottle, 24 g of water as a reaction solvent and 13.212 g of glutaric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed and dissolved at room temperature until homogenous. Then, 10.715 g of benzylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed and stirred for about 5 minutes to obtain a mixed solution. The obtained mixed solution was placed in a refrigerator at 5°C to 10°C and left overnight. The precipitated crystals were separated by filtration, washed with water, and vacuum dried to obtain benzylamine glutarate. The obtained benzylamine glutarate was pulverized by a jet mill pulverization method to obtain benzylamine glutarate with an average particle size of 10 μm.

[0169] Solder particles: SnAgCu solder particles (melting point 220℃, solder particles selected from Mitsui Mining & Smelting Co., Ltd.'s "Sn96.5Ag3Cu0.5", average particle diameter 3μm) SnBi solder particles (melting point 139℃, solder particles selected from "Sn42Bi58" manufactured by Mitsui Mining & Smelting Co., Ltd., average particle diameter 3μm)

[0170] Rubber particles: Polybutadiene rubber particles 1 (Mitsubishi Rayon "C Series", glass transition temperature -60°C, average particle size 0.2μm) Acrylic rubber particles 1 (Mitsubishi Rayon's "W Series", glass transition temperature 0°C, average particle size 0.065 μm) Acrylic rubber particles 2 (Mitsubishi Rayon's "W Series", glass transition temperature 0°C, average particle size 0.1 μm) Acrylic rubber particles 3 (Mitsubishi Rayon's "W Series", glass transition temperature 0°C, average particle size 0.25 μm) Acrylic rubber particles 4 (Mitsubishi Rayon's "W Series", glass transition temperature 0°C, average particle size 0.5 μm) Divinylbenzene polymer particles 1 (Sekisui Chemical's "Micropearl-EL series", no glass transition point, average particle size 3 μm): Glass transition temperature is not observed because a crosslinking agent is included.

[0171] (Average particle size of flux, solder particles and rubber particles) The average particle sizes of the flux, solder particles, and rubber particles were measured using a laser diffraction particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.).

[0172] (Melting point of solder particles and flux) The melting points of the solder particles and the flux were calculated using differential scanning calorimetry (DSC), using an "EXSTAR DSC7020" manufactured by SII Corporation.

[0173] (Examples 1 to 11 and Comparative Examples 1 to 2) (1) Preparation of resin composition (anisotropic conductive paste) The components shown in Tables 1 to 4 below were mixed in the amounts shown in Tables 1 to 4 below to obtain resin compositions (anisotropic conductive pastes).

[0174] (2) Fabrication of connection structure As the first connection target component (circuit board), a glass substrate (thickness: 0.7 mm) having multiple electrodes (first electrode, copper electrode 23 μm wide × 30 μm long × 12 μm thick, 14 μm space between electrodes) on its surface was prepared.

[0175] As the second connection target component (semiconductor chip), a micro LED chip (material: GaN, thickness: 0.01 mm) having multiple electrodes (second electrode, gold electrode measuring 20 μm wide x 20 μm long x 3 μm thick, with a space between electrodes of 10 μm) on its surface was prepared.

[0176] The resin composition (anisotropic conductive paste) immediately after preparation was applied to the upper surface of the glass substrate by screen printing to a thickness of 10 μm to form a resin composition (anisotropic conductive paste) layer. Next, a semiconductor chip was laminated on the upper surface of the resin composition (anisotropic conductive paste) layer by a laser transfer method so that the electrodes faced each other. From that state, the resin composition (anisotropic conductive paste) layer was heated so that the temperature of the resin composition (anisotropic conductive paste) layer reached the melting point of the solder particles 5 seconds after the start of the temperature rise. Furthermore, the resin composition (anisotropic conductive paste) layer was heated so that the temperature of the resin composition (anisotropic conductive paste) layer reached 250° C. 10 seconds after the start of the temperature rise, and the resin composition (anisotropic conductive paste) layer was cured to obtain a connection structure. No pressure was applied during heating.

[0177] (evaluation) (1) Average particle size of the entire flux For the obtained resin composition, the average particle size of the entire flux was measured using a laser diffraction particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.).

[0178] (2) Tack strength of resin composition at 25°C and 50% RH The tack strength of the resulting resin composition was measured at 25° C. and 50% RH by the method described above.

[0179] (3) Screen printability (coating ability) The obtained resin composition (anisotropic conductive paste) was screen printed on a glass substrate using a metal mask with an opening of 114 μm×60 μm and a thickness of 10 μm. The printed surface of 50 printed patterns was observed with a laser microscope immediately after printing to calculate the volume of the resin composition applied to the glass substrate, and the ratio X (%) of the volume of the resin composition applied to the glass substrate to the volume of each opening of the metal mask was calculated. The screen printability was evaluated according to the following criteria.

[0180] [Criteria for Screen Printability] ○○: The percentage of X is 50% or more ○: Proportion X is 30% or more but less than 50% ×: Proportion X is less than 30%

[0181] (4) Solder cohesion In the resulting connection structures (20 pieces), when the portion where the first electrode and the second electrode face each other in the lamination direction of the first electrode, the connection portion, and the second electrode is viewed, the ratio of the area where the solder portion in the connection portion is arranged to the 100% area of ​​the portion where the first electrode and the second electrode face each other was evaluated. The values ​​for the 20 pieces were averaged to find the area ratio Y. From the area ratio Y, the cohesion of the solder during conductive connection was evaluated according to the following criteria.

[0182] [Criteria for determining solder cohesion] ○○: Proportion Y is 70% or more ○: Proportion Y is 60% or more but less than 70% △: Proportion Y is 50% or more but less than 60% ×: Proportion Y is less than 50%

[0183] (5) Captivity of semiconductor chips In "(3) Screen printability", a semiconductor chip was moved by laser transfer at a speed of 1 cm / s on the surface opposite the glass substrate of the resin composition applied by screen printing onto the glass substrate, and 20 semiconductor chips were arranged so that the first electrode of the glass substrate and the second electrode of the semiconductor chip faced each other. Of the 20 semiconductor chips, the percentage Z of the number of semiconductor chips captured at a position within ±3 μm of a predetermined position was calculated. The captureability of the semiconductor chips was evaluated according to the following criteria.

[0184] [Criteria for determining the capture of semiconductor chips] ○○: Proportion Z is 70% or more ○: Proportion Z is 50% or more but less than 70% ×: Proportion Z is less than 50%

[0185] The results are shown in Tables 1 to 4 below.

[0186] [Table 1]

[0187] [Table 2]

[0188] [Table 3]

[0189] [Table 4] [Explanation of symbols]

[0190] 1,1X…Connection structure 2...First connection target member (circuit board) 2a...First electrode 3...Second connection target component (semiconductor chip) 3a...Second electrode 4,4X…Connection part 4A, 4XA...Solder part 4B,4XB…Cured product part 5...Support member 6…Support film 11...Resin composition 11A…Solder particles 11B...Thermosetting component 11C…Rubber particles 11D…Flux 51...Laser irradiation device

Claims

1. The adhesive composition includes a thermosetting component, a flux, solder particles, and rubber particles, The average particle size of the flux is 10 μm or less, A resin composition, wherein the content of the rubber particles is 1% by weight or more and 10% by weight or less, based on 100% by weight of the resin composition.

2. The resin composition according to claim 1, wherein the rubber particles have a glass transition temperature of 25°C or lower.

3. The resin composition according to claim 1 or 2, wherein the rubber particles have an average particle size of 1 μm or less.

4. the thermosetting component comprises a thermosetting compound; The resin composition according to claim 1 or 2, wherein the content of the rubber particles is 2 parts by weight or more and 20 parts by weight or less based on 100 parts by weight of the thermosetting compound.

5. A first arrangement step of arranging the resin composition on a surface of a first connection target member having at least one first electrode on a surface thereof, using the resin composition according to claim 1 or 2; A second arrangement step of moving a second connection target member having at least one second electrode on a surface thereof by a laser transfer method onto a surface of the resin composition opposite to the first connection target member side, and arranging the second connection target member so that the first electrode and the second electrode face each other; A method for manufacturing a connection structure, comprising: a connection process in which a connection portion connecting the first connection target member and the second connection target member is formed from the resin composition by heating the resin composition to a temperature equal to or higher than the melting point of the solder particles, and the first electrode and the second electrode are electrically connected by a solder portion in the connection portion.

6. 6. The method for manufacturing a connection structure described in claim 5, wherein in the second placement step, the second connection target member is moved at a speed of 1 cm / s or more by a laser transfer method onto the surface of the resin composition opposite the first connection target member, and the second connection target member is placed so that the first electrode and the second electrode face each other.

Citation Information

Patent Citations

  • Conductive adhesive composition, connector, and solar cell module

    WO2012102077A1

  • Mirror for reflecting sunlight and reflecting device for solar power generation

    WO2013054869A1

  • Thermosetting adhesive composition and thermosetting adhesive sheet

    WO2016067966A1

  • Filler-containing film

    WO2023054259A1

  • Transfer method, method of manufacturing image display device using the same, and transfer device

    JP2020053558A